The Role of the Agricultural Sector and the Economic Structure of West Java Province - Fajar Andriansyah; Wiwiek Rindayanti; Dominicus Savio Priyarsono (Ekonomis: Journal of Economics and Business, 2026)
The agricultural sector is a primary sector in the economy which is an important foundation in economic growth by contributing to other sectors in the field of industry and services. The West Java agricultural sector is one of the sectors with a high contribution to West Java's GDP. For this reason, this study aims to find out the role of the agricultural sector in the economy of West Java and how the economic structure of West Java is. The research method used was location quotient analysis and shift share analysis with the data used, namely West Java sectoral GDP in 1990-2023. The results of the study found that the agricultural sector in West Java is not a base sector in the economy and does not have sectoral competitiveness, so the role of the agricultural sector only has advantages for the West Java region. The sectors that are the basis and competitive in West Java are the processing industry, construction and several service sectors, this proves that West Java has experienced a transformation of the economic structure from the primary sector to the secondary and tertiary sectors. For this reason, the West Java government needs to re-emphasize policies to increase the output of the agricultural sector which can increase other sectors.